Ultrathin diamond blades for dicing single crystal SiC developed using a novel bonding method. (December 2022) - Li, Mian; Mu, Dekui; Huang, Shuiquan; Wu, Yueqin; Meng, Hui; Xu, Xipeng; Huang, Han
Abstract: Dicing is an important process in the making of semiconductor chips. In recent years, high performance dicing technologies are badly needed for the new-generation wafers such as silicon carbide (SiC) and sapphire as those hard-to-machine brittle materials have posed great challenges for dicing. In this work, a novel bond metal, i.e., Ti-15/75Al binary alloy, was used to fabricate ultrathin diamond blades. The performance of the developed blades was assessed in the dicing of single crystal SiC. The blade using Ti-rich Ti15Al alloy (T-type) as bonding agent was found to produce lower dicing force, smaller chipping size, and higher removal ratio, in comparison to the blades using Al-rich Ti75Al (A-type) and conventional Cu-rich Cu20Sn alloys (C-type) as bond metals. The ground surface produced using the T-type blade was found to be smoother than those generated using the A- and C-type blades. The superior performance of the Ti-rich Ti15Al blade was attributed to the strong interfacial adhesion of diamond grits with the bond alloy. Such adhesion was established through forming titanium carbides at the interface, which helped retention of diamond grits during dicing. The strong adhesion also enabled the blade to possess a relatively high hardness and a sufficiently large porosity in bond matrix, both favored the material removal in the dicing of SiC. Graphical abstract: Unlabelled Image Highlights: Ultrathin diamond blades were successfully fabricated using commercial Cu-based and TiAl binary alloys. Newly developed Ti-based diamond blades showed superior performance in dicing of single-crystal SiC. Interfacial carbides formation thoroughly affects microstructures and mechanical properties of diamond blades. Influence of diamond blades properties on dicing was discussed based on maximum undeformed chip thickness.